Influence of Lithium Content on the Structure and Ionic Conductivity of Perovskite \(La_(2/3) - xLi_3xTiO_3\) Made by Double Mechanical Alloying Method - Trong, Le Dinh (Communications in Physics, 2014)
Perovskite La\(_(2/3) - x\)Li\(_3x\)TiO\(_3\) samples with 0.06 \( ≤ x ≤ 0.15\) were prepared by a double mechanical alloying method. Structure and Li^ + -ion conductive properties of the La\(_(2 / 3) - x\)Li\(_3x\)TiO\(_3\) samples were investigated. Most of the analyzed perovskite samples exhibit a double unit cell. In these samples, a change of symmetry from tetragonal to orthorhombic is observed for sample with lithium content x = 0.06. Structural modifications were obtained mainly due to the cation vacancies ordering along the c-axis, which disappeared gradually when the lithium content increased. At room temperature, the maximum values of grains and grain boundaries conductivities of the La\(_(2 / 3) - x\)Li\(_3x\)TiO\(_3\) samples were found to be of \(1.5× 10^ - 3\) S/cm and \(5.8 × 10^ - 5\) S/cm, respectively. The temperature dependence of ionic conductivity obeyed a non-Arrhenius behaviour. At temperature from 30 to 125\(^°\)C, the activation energy for grain and grain-boundary conductivity was found to be of 0.23 eV and 0.32 eV, respectively.